Determination of phenol in water sample using high performance liquid chromatography / Nazurah Haron - Haron, Nazurah (2017)
Phenol as in water is harmful to living organism yet have a toxicity effect for a long-term exposure. In this research, the analysis was achieved on a C18 column coupled with UV-vis detector (HPLC-UV) for determination of phenol in environmental water while by using solid phase extraction (SPE) as sample preparation technique. The optimized variable involved in SPE and HPLC were as follow: 3 mL was used for load sample volume in SPE, 45 ± 3 drops min-1 was used for sample drop-rate in SPE and 0.35 mL min-1 as flow-rate on eluent in HPLC. The analytical method was validated based on the following parameter: precision, linear range, limit of detection (LOD), limit of quantitation (LOQ) and bias/recovery. A good linear correlation coefficient with R2 = 0.9996 was observed over the range of 0.55 - 30.0 µg mL-1. Both repeatability and reproducibility (RSD, %) were 0.215 and 1.490, respectively. The limit of detection was calculated to be 0.212 µg mL-1, while the limit of quantitation value of the validated method was measured to be 0.642 µg mL-1. Good recoveries were between 81 - 120%. The proposed method was found to be suitable and precise for the determination of phenol in environmental water by using HPLC.